A Prospective Randomized Controlled Study on Multiple Neoadjuvant Treatments for Patients With Stage IB2 to IIA Cervical Cancer. Issue 2 (1st February 2012) - Wen, Hao; Wu, Xiaohua; Li, Ziting; Wang, Huaying; Zang, Rongyu; Sun, Min; Huang, Xiao; Zhang, Zhiyi; Cai, Shumo
Abstract : Objective: Patients with stage IB2 to IIA cervical cancer have a poor survival regardless of what primary treatment is performed. We conducted a study to demonstrate whether neoadjuvant treatment could offer survival benefits to those patients. Methods: Between January 2006 and December 2009, 123 patients with stage IB2 to IIA cervical cancer were enrolled and randomly assigned to receive 1 of the following 4 treatments: radical surgery alone (arm RS), brachytherapy with a total dose of 15Gy to point A followed by radical surgery (arm BT), intravenous chemotherapy with cisplatin 50 mg/m 2 plus 5-fluorouracil 750 mg/m 2 at a 2-week interval for 2 courses followed by radical surgery (arm IVCT), or intra-arterial chemotherapy with the same regimen as the IVCT arm followed by radical surgery (arm IACT). Two weeks after neoadjuvant treatment, all patients underwent evaluation for response and operability. Those who were not amenable to surgery received concurrent chemoradiotherapy. Results: With a mean follow-up of 34.8 months, 120 patients were evaluable. Baseline characteristics were similarly distributed in the 4 arms. Clinical overall response rates were 61.3%, 42.9%, and 79.3% in the BT, IVCT, and IACT groups, respectively. Two patients achieved pathological complete response. Three-year progression-free survival rates were 70.7%, 66.3%, 81.5%, and 79.7% in the RS, BT, IVCT, and IACT arms, respectively ( P = 0.354). Three-year overall survival was 73.3%, 68.3%, 82.9% and 80.4%, respectively ( P = 0.431). Multivariate analysis showed that only lymph node status correlated with progression-free survival. Conclusions: Neoadjuvant treatment had no significant impact on the outcomes of patients with stage IB2 to IIA cervical cancer.